2020
DOI: 10.15842/kjcp.2020.39.4.008
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impact of COVID-19 in South Korea: A Preliminary Study

Abstract: To investigate the impact on mental health of the prolonged COVID-19 outbreak, the current study investigated peritraumatic distress, preventive behaviors, and psychological distress (depression, anxiety symptoms, and suicidal risk) among 1,000 Koreans in May 2020 in comparison with the levels of psychological distress reported among 257 Koreans during the periods before COVID-19 in South Korea and with those reported in other countries during the COVID-19 pandemic. Our results indicated that 27.3%, 34.2%, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 3 publications
2
27
0
1
Order By: Relevance
“…For example, Bezzo et al (2021) , using 9,600 English citizens’ longitudinal data, reported that the level of well-being has decreased after the COVID-19 pandemic and lockdown. In addition, adverse changes in SWB are related to previous research that reported worsening mood, decreased income, and reduced job opportunities ( Bark et al, 2020 , Hacimusalar et al, 2020 ). Thus, our result is meaningful in that we checked the subjective well-being of art therapists, not of the general public.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…For example, Bezzo et al (2021) , using 9,600 English citizens’ longitudinal data, reported that the level of well-being has decreased after the COVID-19 pandemic and lockdown. In addition, adverse changes in SWB are related to previous research that reported worsening mood, decreased income, and reduced job opportunities ( Bark et al, 2020 , Hacimusalar et al, 2020 ). Thus, our result is meaningful in that we checked the subjective well-being of art therapists, not of the general public.…”
Section: Discussionmentioning
confidence: 82%
“…Several studies tracking the effects of COVID-19 found that people suffer from a variety of psychological problems, including anxiety ( Bark et al, 2020 , Erdoğdu et al, 2020 , Huang et al, 2020 , Lee et al, 2020 ), depression ( Lee et al, 2020 , Park, 2020 ), post-traumatic stress symptoms ( Brooks et al, 2020 ), suicide risk ( Bark et al, 2020 ), and fear and distress reactions ( Shigemura, Ursano, Morganstein, Kurosawa & Benedek, 2020 ). Fear of COVID-19 refers to concerns and anxiety relating to COVID-19, which includes psychological and physiological reactions to the COVID-19 news, personal thoughts, and the possibility of infections.…”
mentioning
confidence: 99%
“…The number of confirmed cases is rising rapidly with the emergence of highly contagious variants [ 3 ], and as South Korea has experienced repeated waves of the COVID-19 pandemic, more than 40 million out of 52 million people in South Korea have been vaccinated against COVID-19 [ 4 ]. Due to the pandemic, the governments of every country have implemented measures regarding hand hygiene, social distancing, and the use of personal protective equipment to prevent the spread of the virus [ 5 ], and South Korea is responding to the pandemic by educating the public on preventative measures, and using diagnostic kits to conduct rapid tests [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fear, restrictions in daily life, and needs life were associated with the likelihood of belonging in the anxiety group ( χ 2[20]=263.647, p<0.001). Age-wise, participants who are in their 20's were 2.146 (1/0.446=2.146) times more likely to be in the anxiety group, compared to the participants in their30's (Wald=5.051, exp[B]=0.466, p=0.025), and 2.646 (1/0.378=2.646) times higher likelihood than those in their 50's (Wald=9.616, exp[B]=0.378, p=0.02). COVID-19 related fear was also a significant predictor, with one point increase of fear of being infected, the possibility of belonging in the anxiety group increased by 2.631 times (Wald=25.538, exp[B]=2.631, p<0.001), and one point increase of fear on being quarantined due to infection resulted in 1.568 times higher (Wald=6.676, exp[B]=1.568, p=0.010) possibility of belonging in the anxiety group.…”
mentioning
confidence: 96%
“…13 In South Korea, a study on the mental health of over 1,000 people reported 34.2% and 28.8% of participants experienced a mild or higher level of depression and a mild or higher level of anxiety, respectively, since the spread of the COVID-19. 30 Given the high prevalence, an alternative and/or in-depth analysis is needed to shed light to understanding the vulnerability of at-risk population, other than examining only the average scores of anxiety and depression or using cut-off scores. 10,12,[14][15][16]21,23,24 Currently, few studies have looked into the factors that predict high anxiety and depression.…”
mentioning
confidence: 99%